Pair Interaction Potential Energy Function for H2-H2 from the Viscosity of Normal Hydrogen in the Limit of Zero Density - Haghighi, B.; Mansoori Oghaz, N.; Najafi, M. (Asian Journal of Chemistry, 2012)
An iterative inversion procedure is used to obtain the effective isotropic part of the pair-interaction potential for H2-H2 from the correlation equation for the zero density collision integral of hydrogen, proposed by Assael and coworkers. The Lennard-Jones (12-6) potential energy function is chosen as the initial model potential prerequisite for the method. The comparison of the measured potential with that of HFD-type potential was carried out over a wide range of temperature, i.e., from 20 to 2200 K. The results of this work can satisfactorily be applied in evaluation of both orientation-average viscosity collision integrals and the dimensionless ratios, which are essential parameters in the calculation of other transport properties.